SOVEREIGNS VERSUS BANKS: CREDIT, CRISES, AND CONSEQUENCES. Issue 1 (21st July 2015) - Jordà, Òscar; Schularick, Moritz; Taylor, Alan M.
Abstract: Two separate narratives have emerged in the wake of the Global Financial Crisis. One interpretation speaks of private financial excess and the key role of the banking system in leveraging and deleveraging the economy. The other emphasizes the public sector balance sheet and worries about the risks of lax fiscal policy. However, the two may interact in important and understudied ways. This paper examines the co‐evolution of public and private sector debt in advanced countries from 1870 to 2012. We find that in advanced economies financial crises are not preceded by public debt build‐ups nor are they more likely when public debt is high. However, history shows that high levels of public debt tend to exacerbate the effects of private sector deleveraging after financial crises. The economic costs of financial crises rise substantially if large private sector credit booms are unwound at times when the public sector has little capacity to pursue macroeconomic and financial stabilization.